Tele-immersion - Jayanthila Devi (Institute of Advanced Engineering and Science, 2016)
Tele-immersion is an advanced form of virtual reality that will allow users in different places to interact in real time in a shared simulated environment. Tele-immersion is a technology to be implemented with Internet that will enable users in different geographic locations to come together in a simulated environment to interact. Users will feel like they are actually looking, talking, and meeting with each other face-to-face in the same room.This technology causes users to feel as if they were in the same room. The tele-immersion technology uses a